Alleviated membrane fouling of corundum ceramic membrane in MBR: As compared with alumina membrane. Issue 6 (December 2022) - Tian, Jiayu; Pan, Hui; Bai, Zhaoyu; Huang, Rui; Zheng, Xing; Gao, Shanshan
Abstract: In this study, a novel ceramic membrane was prepared with white corundum powders (CM), and its fouling behavior was evaluated in comparison with an alumina membrane (AM). Although the two membranes possessed almost the same pore size and porosity, the pure water permeability of CM was substantially lower than that of AM, possible due to the irregular pore structure of CM membrane. However, when employed in MBR, the CM exhibited much better antifouling performance with significantly decreased TMP development rate. Dissolved organic foulants (i.e. polysaccharides, proteins and DOC) extracted from the membrane surface of CM was shown to be much lower than that from AM. XDLVO analysis also demonstrated the repulsion force between sludge and CM membrane was stronger. More interestingly, largely different microorganism population was observed to form on the two membranes, which might contribute to the alleviation of CM membrane fouling in MBR. This work provides an easy but effective strategy for improving the antifouling ability of ceramic membrane in MBR. Graphical Abstract: ga1 Highlights: Corundum (CM) and alumina (AM) membranes with different pore structure were prepared. CM possessed similar pore size, porosity, crystal phase but lower permeability to AM. CM exhibited much lower TMP development rate than AM in the same MBR. XDLVO analysis confirmed CM possessed stronger repulsion force to sludge than AM. It was interesting that different microbial community were formed on CM and AM.